TAS1R3 influences GTPase-dependent signaling in human islet β-cells - Veluthakal, Rajakrishnan; Ahn, Miwon; Oh, Eunjin; Thurmond, Debbie C. (Frontiers in Endocrinology, 2025)
BackgroundThe taste receptor type 1 member 3 (TAS1R3), a G protein-coupled receptor (GPCR), is expressed in pancreatic islet β-cells where it may influence intracellular signaling pathways critical for β-cell function. Although TAS1R3 is known to couple to heterotrimeric G-proteins, its potential influence on small GTPases—key regulators of vesicle trafficking, cytoskeletal remodeling, and signal transduction—remains unexplored. Investigating how TAS1R3 modulates small GTPase activity could uncover mechanisms by which β cells regulate insulin secretion and adapt to metabolic cues.ObjectiveWe questioned whether activation of endogenous TAS1R3 in human islets or clonal human β-cells are necessary for glucose-stimulated insulin secretion via activation of small GTPases.Methods and resultsWe found that pharmacological TAS1R3 inhibition (lactisole) in human islets and a human β-cell line diminished glucose-stimulated insulin secretion, attenuated Src family tyrosine kinase signaling, and small GTPase Cdc42 activation. We excluded the requirement for the G protein Gαq/11 in TAS1R3 signaling by using the Gαq/11-specific YM-254890 inhibitor in β-cells. Notably, the significant reduction of TAS1R3 mRNA and protein levels in human type 2 diabetes pancreatic islets, which could be replicated in otherwise healthy cells exposed to diabetogenic stimuli, indicates that the TAS1R3 deficit may be a consequence of diabetogenic stimuli.ConclusionOverall, our results suggest that TAS1R3 plays an essential role in GTPase signaling in islet β-cells adding to the growing list of proteins that play a vital role in islets as therapeutic targets in type 2 diabetes.